2022
DOI: 10.1128/mbio.01311-22
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Vaccine-Induced SARS-CoV-2 Variant-Specific Immunity in Children

Abstract: This work evaluated the immune response induced by two doses of CoronaVac separated by 4 weeks in healthy children and adolescents in Chile. To date, few studies have described the effects of CoronaVac in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…However, inactivated vaccines contain all the structural proteins in the SARS‐CoV‐2 virion, which may elicit multiprotein T cell responses. An activation‐induced marker expression assay revealed two doses of CoronaVac induced OX40 + CD137 + CD4 + T cells against S, N, and M in children aged 3–17 years 59 . The responses against S between children aged 3–11 and adolescents aged 12–17 were similar.…”
Section: Immune Responses To Inactivated Virus Vaccinesmentioning
confidence: 90%
See 3 more Smart Citations
“…However, inactivated vaccines contain all the structural proteins in the SARS‐CoV‐2 virion, which may elicit multiprotein T cell responses. An activation‐induced marker expression assay revealed two doses of CoronaVac induced OX40 + CD137 + CD4 + T cells against S, N, and M in children aged 3–17 years 59 . The responses against S between children aged 3–11 and adolescents aged 12–17 were similar.…”
Section: Immune Responses To Inactivated Virus Vaccinesmentioning
confidence: 90%
“…Inactivated COVID‐19 vaccines also demonstrated robust antibody responses in pivotal trials 32,33,54–59 . The notable similarity between the inactivated and mRNA vaccines is that immune responses to both appeared to be age‐dependent.…”
Section: Immune Responses To Inactivated Virus Vaccinesmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, cytotoxic T cells can disinfect by killing virus-infected cells. Studies have confirmed that specific T-cell immunity targeting SARS-CoV-2 proteins plays an important role in viral clearance and prevention [78,79]. Some scholars found that neutralizing antibody levels significantly decreased in recovered patients > 3 months after infection, but T-lymphocyte immunity persisted after at least 10 months [80][81][82] and is expected to be maintained for many years [83].…”
Section: Coping Measuresmentioning
confidence: 93%